Urgensi Pendidikan Karakter Islam dalam Menghadapi Tantangan Era Digital bagi Generasi Z - Yusriyah Yusriyah; Akramun Nisa (Yayasan Syamil Quran Nunukan, 2024)
This article discusses the importance of character education in dealing with the negative impact of technological developments in the digital era, especially for generation Z. Rapidly developing technology provides broad and fast access to information, but also raises challenges such as distraction and exposure to negative content which can damage the character of generation Z. Character education that is integrated with Islamic religious values ​​plays an important role in forming individuals with noble and devout morals. This research highlights that effective character education, based on the teachings of the Qur'an and Hadith, can help generation Z develop traits such as honesty, justice, patience and compassion. These values ​​are important for creating individuals who are not only intellectually intelligent but also moral and ethical, and able to face the challenges of the VUCA (Volatile, Uncertain, Complex, Ambiguous) era wisely. Character education in Islam aims to form a just, prosperous and harmonious society.